Pentecostal church leaders’ support to children in need of care and protection - Andrew Spaumer; Azwihangwisi H. Mavhandu-Mudzusi (HTS Teologiese Studies/Theological Studies)
Churches are considered one of the important structures responsible for providing care and support to vulnerable populations. One such population are children in need of care and support. This article presents the support provided by Pentecostal religious leaders to children needing care and protection. The study was conducted in Pentecostal churches in Tshwane Metropolitan Municipality, which is found in Gauteng province, South Africa. This qualitative study used an interpretative phenomenological analysis design. Data were collected from nineteen purposively selected leaders in Pentecostal churches using face-to-face semi-structured interviews. Data analysis was guided by the interpretative phenomenological analysis framework for data analysis. Findings indicate that religious leaders within Pentecostal churches are involved in providing care and support to children in need of care. The process they are engaged in include proper identification of those children, attending to physical, psychosocial and spiritual needs. However, each religious leaders use their approach depending on the relationship they have with members of government institutions such as police services and social workers. In order to enhance the support provided the children in need of care and protection, by religious leaders within Pentecostal churches, it is recommended that religious leaders are well informed about the role of different members of multidisciplinary teams such as social workers, psychologists, police officers, parents and other community structures. Moreover, there should be formalised collaboration and referral processes that will ensure that the child’s rights are not further violated in the process of provision of support.